2001
DOI: 10.1039/b106366a
|View full text |Cite
|
Sign up to set email alerts
|

The first observation of the [Cp3Mn]– anion; structures of hexagonal [(η2-Cp)3MnK·1.5thf] and ion-separated [(η2-Cp)3Mn]2[Mg(thf)6]·2thf

Abstract: Hexagonal [(eta 2-Cp)3MnK.1.5thf] 1 and ion-separated [(eta 2-Cp)3Mn]2[Mg(thf)6].2thf 2 are obtained from reactions of CpK and Cp2Mg, respectively, with manganocene, Cp2Mn; they are the first complexes to be structurally characterised containing the [Cp3Mn]- anion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 23 publications
(8 reference statements)
4
24
0
Order By: Relevance
“…3) where the cation is formed by an octahedral magnesium surrounded by six molecules of THF whereas the anionic moiety consists of two zinc atoms bonded to two chlorine bridges and two terminal ones in a distorted tetrahedral geometry. Several examples of other mixed-metal compounds containing either one of these two ions, separately but never together, have been reported (23)(24)(25)(26). However, surprisingly a search of the Cambridge Crystallographic Database revealed that the 1∶2, Mg∶Zn stoichiometry found in compound 3 is extremely rare across the whole of mixed magnesium-zinc chemistry, with only three such compounds structurally characterized to date (27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…3) where the cation is formed by an octahedral magnesium surrounded by six molecules of THF whereas the anionic moiety consists of two zinc atoms bonded to two chlorine bridges and two terminal ones in a distorted tetrahedral geometry. Several examples of other mixed-metal compounds containing either one of these two ions, separately but never together, have been reported (23)(24)(25)(26). However, surprisingly a search of the Cambridge Crystallographic Database revealed that the 1∶2, Mg∶Zn stoichiometry found in compound 3 is extremely rare across the whole of mixed magnesium-zinc chemistry, with only three such compounds structurally characterized to date (27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to the coordination found in other cyclopentadienyl potassium metalates. [18] Whereas M(C 5 H 5 ) 3 À ions are now relatively common for main-group elements, [18b, 19, 20] and are also known for some dand f-block elements, [18c, 21] (Figure 3 À the calculated Zn À C distances and Zn-C-ring angles are, respectively, 2.14 and 1028. In the computed models, the distance between the metal and the two carbon atoms adjacent to the zinc-bound carbon are longer than 2.74 .…”
Section: X]mentioning
confidence: 99%
“…[9] The extent of aggregation in these so-called "paddlewheel" anions (i.e., the value of n) is governed by the stoichiometry of the reagents and the thermochemical radius of the counterion (i.e., the nature of the co-solvent, L, and the value of x). The latter signifies the importance of lattice energies in determining the outcomes of the reactions.…”
Section: Introductionmentioning
confidence: 99%